VOLATILE COMPOUNDS DURING THE RIPENING OF COLOMBIAN SOURSOP (Annona muricata L. cv. Elita) - MÁRQUEZ C., Carlos J.; JIMÉNEZ, Aleyda M.; OSORIO, Coralia; CARTAGENA V., José R. (Vitae, 2011)
Fruits of soursop (Annona muricata L. cv. Elita) were evaluated at different ripening stages to determine the changes in their physicochemical characteristics: total soluble solid content, percentage of acidity, pH, and ripeness index. The change in volatile compounds were determined through Headspace-Solid Phase Microextraction and subsequent Gas Chromatography-Mass Spectrometry analyses. The volatile compounds were identified through the comparison of their chromatographic and spectral properties against the ones exhibited by reference substances. The sensorial quality factors showed values that changed according to the ripening stage. It was established that the ester levels, particularly those from C6, C4, and C8 saturated and unsaturated aliphatic acids, increased with ripening. C6 aliphatic compounds, such as (Z)-3-hexenol and (Z)-3-hexenal, were observed to be the major volatile constituents in the green stage. In contrast, methyl hexanoate and methyl (E)-2-hexenoate were the main volatile in ripe, overripe and half ripe fruits. The overripe stage was characterized by an increase in the ethyl acetate, methyl butanoate and ethyl butanoate levels, and the appearance of butanoic and hexanoic aliphatic acids. These facts could be used as an indicator of the beginning of the fermentation stage and the loss of fruit sensory quality.